PENGARUH SELF CONTROL DAN LITERASI KEUANGAN TERHADAP PENGELOLAAN KEUANGAN MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Yulianti, Yulianti; Witarsa, Witarsa; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Students who lack financial management expertise have a diminished sense of accountability for handling their own money. By developing self-control in meeting needs and increasing financial literacy, students can handle their finances more effectively and efficiently. The purpose of this study is to ascertain how self-control and financial literacy affect the financial management of FKIP UNTAN students studying economics education. Multiple linear regression in a quantitative form is the study methodology employed. Active economics education students in the Regular A and PPAPK classes in 2021, 2022, and 2023 served as the data sources, and Google Forms surveys were used to collect the data 125 economics education students from the 2021, 2022, and 2023 classes made up the sample. Heteroscedasticity, multicollinearity, and normalcy are examples of traditional assumption testing. Among the tests used are the F test, t test, and R2 test. The results of the study indicate that: 1) self-control has a substantial impact on financial management (0.701) at a significance level of 0.000